Frozen section library liver, extrahepatic biliary tree, and gallbladder - Yantiss, Rhonda K. (Frozen section library., 2011)
"The Frozen Section Library series" provides concise, user-friendly, site specific handbooks that are well illustrated and highlight the pitfalls, artifacts and differential diagnosis issues that arise in the hurried frozen section scenario. "Frozen Section Library: Liver, Extrahepatic Biliary Tree and Gallbladder" provides a convenient reference for use during intraoperative consultation. This volume addresses commonly encountered challenges, such as the diagnosis of primary and secondary hepatic neoplasms and assessment of gross abnormalities of the gallbladder.